Maintaining External Connections During Incarceration: Latent Class Analysis of Visitors for Women and Men in Prison - Hickert, Audrey (Crime & delinquency, 2022)
Research on the prison visitation context has recently grown, yet little is known about the overall composition of who visits. This paper describes visit groups using latent class analysis (LCA) separately for women and men incarcerated two or more years in New York State. In this context where policies support frequent in-person visits, many maintain large, diverse groups of external connections. Although theory suggests that some groups may be more beneficial than others (e.g., prosocial influence or social support), visitor classes did not predict recidivism, but recidivism was higher for those with no/few visits. Policies that restrict visitor types or amounts may diminish valuable external social ties that can be maintained and offer ongoing support in more visit-positive regimes.